Ultraviolet-Related Ocular Disease: Tissue-Specific Effects, Outdoor Exposure and Prevention - A Literature Review - Borowska, Aleksandra; Kobryń, Pola; Ocicki, Dawid; Bojarski, Michał; Kwiatkowski, Michał; Musielak, Michał; Kobryń, Iga; Zybert, Aleksandra; Nowiński, Igor; Grabowski, Jakub (Quality in Sport, 2026)
Background. Ultraviolet radiation (UVR) is a well-established cause of skin damage, photoaging and cancer but its ocular effects are less consistently addressed in prevention. The cornea, conjunctiva, limbus and crystalline lens are exposed to wavelength-dependent photochemical stress, particularly during outdoor activities and sports. Aim. To review the pathophysiology, clinical features, epidemiology and prevention of UV-related ocular disease, with emphasis on wavelength-dependent exposure, peripheral light focusing and high-risk settings such as outdoor and sports environments. Key conditions include photokeratitis, pinguecula, pterygium, cortical cataract and age-related macular degeneration. Material and methods. A literature review of scientific publications on UV-related ocular disease was conducted, focusing on major disorders, mechanisms of damage and ocular photoprotection. Results. UVA (315–400 nm), UVB (280–315 nm) and UVC (100–280 nm) differ in atmospheric transmission and tissue absorption. UVB is mainly absorbed by the cornea and causes acute epithelial injury, while chronic exposure contributes to conjunctival degeneration, limbal remodeling and lens opacification. Peripheral light focusing increases irradiance at the nasal limbus and lens cortex, consistent with the distribution of pinguecula, pterygium and cortical cataract. Outdoor sports increase cumulative UV exposure. Conclusions. UV-related ocular disease represents tissue-specific responses to a shared environmental exposure. Prevention is essential in outdoor and sports settings and requires certified UV-filtering eyewear, proper frame design and regular use. Lens tint alone is insufficient. Keywords: ultraviolet radiation; UVA; UVB; photokeratitis; pinguecula; pterygium; cataract; age-related macular degeneration; ocular photoprotection.